Smallest known raptor tracks suggest microraptorine activity in lakeshore setting. Issue 1 (December 2018) - Kim, Kyung; Lim, Jong; Lockley, Martin; Xing, Lida; Kim, Dong; Piñuela, Laura; Romilio, Anthony; Yoo, Jae; Kim, Jin; Ahn, Jaehong
Abstract Ongoing studies of a multiple track-bearing horizons from massive excavations in the Jinju Formation (Lower Cretaceous) of South Korea have yielded a remarkable diversity of avian, non-avian dinosaur, pterosaur, crocodilian and mammal tracks, many very small and well preserved. Here we report diminutive, didactyl tracks ( 1.0 cm long) assigned to a new dromaeosaurid ichnogenusDromaeosauriformipes, which resembles the larger, but still quite small, ichnogenusDromaeosauripus, also from the same formation only 30 km away. These diminutive tracks are consistent with the foot size of smaller dromaeosaurid taxa like Early CretaceousMicroraptor from China, and may represent diminutive species or juveniles of larger species. The association of tracks with lakeshore sediments is consistent with the evidence thatMicroraptor was a fish eater. Two trackways and isolated tracks indicate variable trackmaker gaits and speeds. If oviparous, as assumed for most non-avian dinosaur neonates, the trackmakers must have hatched from tiny eggs. Previous studies of the Korean Cretaceous indicate the presence of other diminutive ( 1.0 cm long) theropod tracks (Minisauripus ). Such occurrences strongly suggest that small tracks attributed to juveniles, or very small tetrapod species, are more common than previously supposed especially where suitable preservation conditions prevailed.